Challenge accepted: employing reading comprehension strategies in training your brain into becoming a better reader - Radostina Iglikova (Studies in Linguistics, Culture, and FLT, 2016)
The following article provides a brief overview of the specificities of the processes of reading and comprehension as a starting point for a discussion of the 8 reading comprehension strategies deemed most successful. Furthermore, it provides a list of practical guidelines for the application of each of these strategies.